2004
DOI: 10.1016/j.physletb.2003.10.108
|View full text |Cite
|
Sign up to set email alerts
|

Update: A reanalysis of hadronic cross section measurements at CMD-2

Abstract: The updated results of the precise measurements of the processes e + e − → ρ → π + π − , e + e − → ω → π + π − π 0 and e + e − → φ → K 0 L K 0 S performed by the CMD-2 collaboration are presented. The update appeared necessary due an overestimate of the integrated luminosity in previous analyses.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
217
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(228 citation statements)
references
References 16 publications
(22 reference statements)
11
217
0
Order By: Relevance
“…An intermediate improvement has appeared in the published document [3] and an additional improvement has become available in 2004 [4]. We have concluded that the most recent CMD-2 results imply only a small change in the estimate of the hadronic contribution [5].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…An intermediate improvement has appeared in the published document [3] and an additional improvement has become available in 2004 [4]. We have concluded that the most recent CMD-2 results imply only a small change in the estimate of the hadronic contribution [5].…”
mentioning
confidence: 98%
“…We obtain a value of the hadronic contribution to the running of the QED fine structure constant of [1] to 0.00 347 and the relative uncertainty has decreased from 2.3% to 0.9%. The change of the uncertainty corresponds to the change of precision from the preliminary CMD-2 [2] data to the combination of published CMD-2 [4] and KLOE [6] data. The change of the value and the uncertainty of the hadronic contribution to the running of the QED fine structure constant at m 2 Z is very small.…”
mentioning
confidence: 99%
“…The analysis based on the τ decay data and recent e + e − data from SND collaboration [5] provide the SM results which are in good agreement with the experimental one. The results based on the e + e − data published by the CMD [12] and KLOE [13] data support bigger difference between SM prediction and (g-2) Collaboration result. Theoretically, the τ decay data is found [21] to be more compatible with expectations based on high-scale α s (M Z ) determinations; the electroproduction data (CMD, KLOE), in contrast, requires significantly lower α s (M Z ).…”
Section: Phenomenological Estimates Of the Lo Hadronic Contributions mentioning
confidence: 63%
“…The most recent estimates of the dispersion integral for the 2π-channel in the energy range 0.39 < t π < 0.97 GeV 2 which are based on the e + e − experimental results are following a ππ µ = (378.6 ± 5.0) · 10 −10 CMD2 (2003) [12], a ππ µ = (375.6 ± 5.7) · 10 −10 KLOE (2004) [13], a ππ µ = (385.6 ± 5.2) · 10 −10 SND (2005) [5].…”
Section: Phenomenological Estimates Of the Lo Hadronic Contributions mentioning
confidence: 99%
“…Alternatively, CVC relates the properties of the π + π − system produced in e + e − → π + π − to those of the π − π 0 system produced in τ − → π − π 0 ν τ decay; thus, using CVC and correcting for isospin-violating effects, τ data have also been used to obtain a more precise prediction for a had,LO µ [2,4]. Recently, data on e + e − → π + π − has become available from the CMD-2, KLOE, and SND experiments [5,6,7,8]. Data on τ decays is available from the ALEPH [9,10], CLEO [11], and OPAL [12] experiments.…”
Section: Introductionmentioning
confidence: 99%